2016
DOI: 10.1148/radiol.2016164007
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer Structural Connectome: Changes in Cortical Network Topology with Increased Amyloid Plaque Burden

Abstract: For the Alzheimer's Disease Neuroimaging InitiativePurpose:To evaluate differences in the structural connectome among patients with normal cognition (NC), mild cognitive impairment (MCI), and Alzheimer disease (AD) and to determine associations between the structural connectome and cortical amyloid deposition. Materials and Methods:Patients enrolled in a multicenter biomarker study (Alzheimer's Disease Neuroimaging Initiative [ADNI] 2) who had both baseline diffusion-tensor (DT) and florbetapir positron emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
(32 reference statements)
2
20
0
1
Order By: Relevance
“…This study is also in agreement with a very recent study [48] in which a related dataset and connectivity analysis were also used. The authors of this study concluded that the beta-amyloid burden, as measured by 18F-AV-45, was related to changes in structural connectivity metrics.…”
Section: H Overall Connectivity Changes In Adsupporting
confidence: 92%
“…This study is also in agreement with a very recent study [48] in which a related dataset and connectivity analysis were also used. The authors of this study concluded that the beta-amyloid burden, as measured by 18F-AV-45, was related to changes in structural connectivity metrics.…”
Section: H Overall Connectivity Changes In Adsupporting
confidence: 92%
“…From a neuropathological point of view, intracellular neurofibrillary tangles (NFTs) are first found in the EC, then in the HIP and later on in other regions . As the selected epicenter is noted to be more involved in tau protein than beta accumulation, especially in early stages of AD , where a random distribution of cortical amyloid beta deposits has been observed, the results of our study possibly relate to the effects of tau protein. The distribution of NFTs in the human cerebral cortex is noted to closely match, on a laminar and regional basis, that of pyramidal neurons enabling cortico‐cortical connections between and within hemispheres , observations consistent with a latent interplay between cytoarchitectural features of cortical regions and their global cortico‐cortical connectivity fingerprint .…”
Section: Resultsmentioning
confidence: 51%
“…Therefore, brain connectomics studies designed to examine disruptions of connectivity in AD have become increasingly common [2][3][4][5][6][7]. Brain connectomics is a field of study that uses graph theory to analyze the ensemble of brain connectivity networks, including functional networks.…”
Section: Introductionmentioning
confidence: 99%